Comparison of Chemotherapy Regiments between CisplatinEtoposide and Cisplatin-Docetaxel on 2-Year and ProgressionFree Survival in Late-Stage Non-Small Cell Lung Cancer Patients - Harahap, Salman Paris; Sutandyo, Noorwati; Rumende, Cleopas Martin; Shatri, Hamzah (UI Scholars Hub, 2016)
Introduction. Chemotherapy is one of therapy choices for the advanced Non-Small Cell Lung Cancer (NSCLC). The success in therapy is measured with the 1-year survival, 2-year survival and the Progression Free Survival (PFS). The success is influenced by many factors: resistant to the citostatic, dosage, administer intensity, chemotherapy regiment, type histology, stage, performance status, comorbidity and social economic. In Indonesia, funding and chemotherapy regiment become the challenge for the success of therapy. Methods. The study used the Retrospective Cohort study with survival analysis. The Patients included in this study were the advanced NSC Lung Cancer (At least Stadium IIIa) who came to RSKD and RSCM during Jan 2006 – December 2010 for their first chemotherapy until finished the cycle (6 times) and had monitored for 2 years. Data was analyzed using cox regression analysis SPSS 16.0, and featured on the Kaplan Meier Curve. Results. Fifty five patients used EC and the other 55 patients used DC. There’s difference on survival where 1 year survival EC is 30,9% and DC is 47,3%, with p 0.030. Two year survival CE is 0% and for DC is 5.5%, with p 0.003. Also with the Median time survival between EC for 27 weeks and DC for 38 weeks with p < 0.016. Compared to DC, EC chemotherapy can increase the death risk by HR 1,684 (CI 95% 1,010-2,810), twenty four weeks PFS with EC is 54.5%, DC is 32.7% with p= 0.022. Conclusions. The survival with cisplatin-docexatel is better compared to cisplatin-etoposide, this applies to PFS as well.